Facial emotion recognition in alcohol and substance use disorders: A meta-analysis. (December 2015) - Castellano, Filippo; Bartoli, Francesco; Crocamo, Cristina; Gamba, Giulia; Tremolada, Martina; Santambrogio, Jacopo; Clerici, Massimo; Carrà, Giuseppe
Highlights: Previous research on AUDs/SUDs and FER showed inconclusive results. Our meta-analysis found that people with AUDs/SUDs had worse FER relative to controls. We found high heterogeneity, but no risk of publication bias across studies. Future research should clarify the role of specific AUDs/SUDs clinical issues. Abstract: People with alcohol and substance use disorders (AUDs/SUDs) show worse facial emotion recognition (FER) than controls, though magnitude and potential moderators remain unknown. The aim of this meta-analysis was to estimate the association between AUDs, SUDs and FER impairment. Electronic databases were searched through April 2015. Pooled analyses were based on standardized mean differences between index and control groups with 95% confidence intervals, weighting each study with random effects inverse variance models. Risk of publication bias and role of potential moderators, including task type, were explored. Nineteen of 70 studies assessed for eligibility met the inclusion criteria, comprising 1352 individuals, of whom 714 (53%) had AUDs or SUDs. The association between substance related disorders and FER performance showed an effect size of −0.67 (−0.95, −0.39), and −0.65 (−0.93, −0.37) for AUDs and SUDs, respectively. There was no publication bias and subgroup and sensitivity analyses based on potential moderators confirmed core results. Future longitudinal research should confirm these findings, clarifying the role of specific clinical issues of AUDs and SUDs.